The Soul: Discipleship that Fosters an Integrated Soul - Lanker, Jason (Christian education journal, 2019)
Most often when the soul is mentioned, the Church's only concern seems to be in "saving" it. Yet, the scriptures regularly refer to the care of the soul in much broader, and more holistic ways. So if we are ever going to help the Church to see regularly the soul's transformation, we must first have a clearer conception of it and the general process of its change. This article attempts to clarify those foundations and to draw meaningful applications for its ongoing discipleship.